Effects of a cooling channel on the creep damage and failure probability of planar solid oxide fuel cells - Luo, Yun; Chen, Xuqian; Liu, Rongjun; Jiang, Wenchun (Frontiers in Materials, 2023)
A solid oxide fuel cell (SOFC) is an all-solid-state chemical power generation device that converts chemical energy into electrical energy in an efficient and environmentally friendly way in medium- and high-temperature environments. However, the thermal stresses and creep damage are inevitably generated at high temperatures, which easily leads to mechanical failure or failure of the whole SOFC stack. Reducing the thermal stress generated by the uneven temperature distribution inside the SOFC stack has become a key problem to be solved urgently. In this paper, the thermal stress, creep damage, and failure behavior under their working conditions were analyzed by the finite element method. Then, the cooling channel was proposed to reduce the thermal stress and creep damage. The results show that adding the cooling channel to SOFC stack can reduce the creep damage and failure probability. The lower the cooling temperature, the better the cooling effect, and the lower the creep damage and failure probability.